Introduction to mechatronics - Kuttan, Appuu (Oxford higher education., 2007)
"Introduction to Mechatronics discusses the design of simpler, more economical, reliable, and versatile systems based on the principles of mechanics, electronics, and computing. The book describes the historical development of mechatronic systems and provides a basic background for mechatronic systems engineering. The introductory topics on mechatronics are dealt with in the book and it will prove to be very useful for undergraduate and postgraduate students as well as practice engineers. Beginning with the basic concepts of mechatronic systems, the book provides a comprehensive coverage of topics including system modelling and analysis, application of microprocessors and microcontrollers in mechatronic systems, sensors and actuators in mechatronic systems, intelligent systems for accurate operation of mechatronic systems, and application of mechatronic systems in autotronics, bionics, and avionics."--Publisher's website.